Mind Mapping Practices in Collocation Teaching and Learning: In Focus of EFL Contexts - Berta, Getaneh (STAIN Majene, 2024)
The objective of the study was to explore EFL teachers’ and EFL students’ adjective-preposition and verb-noun combinations collocations in teaching and learning practices through mind mapping. The study was conducted in Majete General Secondary School which is found in North Shoa, Amhara Region, Ethiopia. Eighty-three grade twelve EFL students who were chosen through a simple random sampling technique participated in the study. Moreover, two EFL teachers also took part by providing their views on the issue. Additionally, data were collected through questionnaire, interview and observation. Consequently, quantitative and qualitative data analysis methods were used to analyze the data obtained from the sources. As the findings indicate, even though EFL teachers and EFL students taught and learned adjective-preposition and verb-noun combinations collocations, neither the EFL teachers aided the lessons through mind mapping nor the EFL students use a mind map as note-taking technique. Hence, since the diagram plays a pivotal role in helping EFL teachers to deliver language contents interestingly and EFL students learn and remember language contents through association, textbook writers and pedagogues should present collocations of language contents through mind mapping. Additionally, it is recommended that EFL teachers and EFL students deploy it in their language teaching and learning practices.